2021
DOI: 10.1088/1755-1315/766/1/012074
|View full text |Cite
|
Sign up to set email alerts
|

Research Status of Generation and Management of Garden Waste in China: A case of Shanghai

Abstract: In the present study, by complying with the panel data of China’s urban garden waste emissions from 2011 to 2019, a dynamic characteristic analysis and a temporal and spatial analysis are conducted on the existing status of garden waste emissions of our nation. In addition, an in-depth study is carried out on the spatial distribution characteristics of garden waste emissions. Moreover, the current situation of garden waste management in Shanghai is analysed, the lack of garden waste management in typical citie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…With the growth of urban green areas in China, the amount of garden waste has also increased as a result of landscape maintenance. In the decade from 2011 to 2019, the amount of garden waste in China surged from 22.453 million tons in 2011 to 33.134 million tons in 2019 [1]. However, the recycling rate of garden waste in China is less than 10%.…”
Section: Introductionmentioning
confidence: 99%
“…With the growth of urban green areas in China, the amount of garden waste has also increased as a result of landscape maintenance. In the decade from 2011 to 2019, the amount of garden waste in China surged from 22.453 million tons in 2011 to 33.134 million tons in 2019 [1]. However, the recycling rate of garden waste in China is less than 10%.…”
Section: Introductionmentioning
confidence: 99%
“…(5) Fallen leaves According to [37], more than 30 million tons of green waste are produced every year in China, with fallen leaves and tree pruning waste representing dominant forms. Another study showed that bulked aerobic composting with fallen leaves has potential for kitchen waste disposal [19], then fallen leaves and KW fertilizer may have combined effects on the vegetation performance of VC.…”
Section: Admixturesmentioning
confidence: 99%
“…This information is supported by the results of research by Adeleke et al [11] that the effective factor of generation is influenced and composition follows different patterns in different places at different locations at different times and seasons. Studies related to waste generation were reported by Shu et al [12][13][14].…”
Section: Introductionmentioning
confidence: 99%